2016
DOI: 10.14527/kuey.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

The Problems Related to Classroom Management Encountered in The Process of Using E-Learning Systems and Solution Suggestions

Abstract: Kuram ve Uygulamada Eğitim Yönetimi 2015, Cilt 21, Sayı 4, ss: 453-470 w w w . k u e y . n e t Atıf için/Please cite as:Dinçer, S. ve Yeşilpınar-Uyar, M. (2015). E-öğrenme sistemlerinin kullanımı sürecinde karşılaşılan sınıf yönetimi ile ilişkili sorunlar ve çözüm önerileri. ÖzAraştırmada eğitim fakültelerinde görev yapan öğretim elamanlarının e-öğrenme sistemlerinin kullanımı sürecinde karşılaştıkları sorunların sınıf yönetimi bağlamında incelenmesi ve bu sorunların çözümüne yönelik önerilerinin belirlen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, it should be paid attention to ensure that the teachers establish a common goal, determine assessment and evaluation levels in the planning and programming of teaching, and provide feedback about the students' level of readiness. During the detailed arrangement of the plans, the students' requests and concerns should also be taken into account (Dinçer & Yeşilpınar-Uyar, 2015).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Nevertheless, it should be paid attention to ensure that the teachers establish a common goal, determine assessment and evaluation levels in the planning and programming of teaching, and provide feedback about the students' level of readiness. During the detailed arrangement of the plans, the students' requests and concerns should also be taken into account (Dinçer & Yeşilpınar-Uyar, 2015).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…In virtual classrooms, on the other hand, the fact that communication is not face-to-face poses a challenge that is reflected in the management of virtual classrooms (Almonacid-Fierro et al, 2021;Can, 2020;Sabancı & Yılmaz, 2021). In addition, technical problems in the virtual classroom environment, the teacher's body language and the attractiveness of the materials used in the classroom environment, the number of students, etc., may also negatively affect communication with students (Cornelius, 2014;Çoruhlu & Uzun, 2021;Dinçer & Uyar, 2016;Goektaş & Sırakaya, 2021;Hilli, 2020;Kalelioğlu et al, 2016;Phelps & Vlachopoulos, 2020;Yılmaz et al, 2022;Yueksel, 2021). To effectively manage virtual classrooms, the main concern is to keep the number of students manageable (Schlusmans et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors influential on attitudes towards e-learning management system is the level of knowledge about computer and Internet use. Studies conducted in the field demonstrated that students' low level of knowledge about devices and tools regarding information technologies increase their level of related anxiety (Dinçer et al [14]; Chan et al [11]; Thatcher et al [53]). In the present study, no significant difference was found between the students' attitudes towards e-learning management system with respect to their weekly Internet use.…”
Section: Discussionmentioning
confidence: 99%